Understanding Design Empowerment through ICT-based Platforms in European Cities - Gun, Ahmet; Demir, Yuksel; Pak, Burak (Editora Blucher, 2019)
The use of ICT-based participation tools in urban design has gained importance in the last decade. In order to enable the citizens and other stakeholders to participate in city-making processes, a wide range of ICT-enabled participatory tools, techniques, and applications have been developed.. Many studies have reported that the use of these participatory platforms has led to positive outcomes but the platforms' potentials and limits for facilitating different levels of design empowerment still remain unknown. In this context, this study aims to determine how these platforms empower citizens' engagement and identify the key factors that can facilitate better participation practices. This research analyses 25 ICT-based participation platforms by focusing on 4 key criteria:(1) their objectives, (2) the design action phases in which they are designated to be used, (3) their desired levels of design empowerment, and (4) offered functions. Our study reveals that more than three-fourth of analysed platforms still complemented by off-line participation activities. Empowering citizens to design independently is still a challenging task so just three platforms (12%) allow users to create their own plans and visions. Finally, we identify several influence factors for better ICT-based participatory design practices.
Keywords: ICT-based participation; Participatory platforms; Technology; Science & Technology; Arts & Humanities; Social Sciences; Engagement; Education & Educational Research; urban design; Architecture; Computer Science; Computer Science, Interdisciplinary Applications; citizen empowerment; participatory design; Education, Scientific Disciplines